Pengungkapan Intellectual Capital Dan Corporate Governance Terhadap Biaya Ekuitas Dengan Pendekatan Model Ohlson - Rivandi, Muhammad; Meirina, Elsa; Zulvia, Dewi; Susanti, Febsri (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2024)
Cost of equity is a cost concept used in determining the amount of costs that will be incurred by the company to fund providers or investors to then determine the average cost of capital of all funds that have been used. The cost of equity measurement used in this study is the Ohlson model. This study aims to analyze the effect of intellectual capital disclosure, independent commissioners, and leverage on the cost of equity. The sample of companies used by LQ45 companies listed on the Indonesia Stock Exchange in 2020-2023 was selected using purposive sampling techniques. The analysis method uses panel data regression. The results of this study show that 1) intellectual capital disclosure has no effect on the cost of equity, 2) independent commissioners have a negative and significant effect on the cost of equity and 3) leverage has no effect on the cost of equity. The implications of the research are expected to be used as a basis in future research and provide an overview of intellectual capital disclosure and corporate governance on the cost of equity through the Ohlson model approach